Agronomic performance of mini-tomato hybrids from dwarf lines - Rafael Resende Finzi; Gabriel Mascarenhas Maciel; Ernani Clarete da Silva; Jose Magno Queiroz Luz; Monique Ellis Aguilar Borba (Ciência e Agrotecnologia)
ABSTRACT Little is known about the commercial potential of mini-tomato hybrids obtained from one dwarf parent. Thus, our objective was to evaluate the agronomic performance of mini-tomato hybrids obtained by crossing a dwarf line (A) with normal lines with indeterminate (I), determinate (D) and semi-determinate (SD) growth habits. The experiment was conducted in a greenhouse at the Estação Experimental de Hortaliças at the Universidade Federal de Uberlândia-UFU in Monte Carmelo, Brazil. The experiment was completely randomized with 17 treatments and four repetitions. The genetic material consisted of 16 experimental mini-tomato hybrids from the tomato germplasm bank at UFU, and a commercial hybrid (Mascot) as a control. The following variables were used to evaluate agronomic performance: fruit weight (g); number of fruits plant-1; productivity (kg plant-1); number of bunches plant-1; number of fruits bunch-1; stem diameter (mm); distance between first bunch and soil (cm); internode length (cm) and total soluble solids (°Brix). The growth habit of the parents influenced the performance of the hybrids. In general, the mini-tomato hybrids from dwarf lines differed from the control with respect to all variables except number of fruits plant-1, number of fruits bunch-1 and stem diameter. On average, hybrids from dwarf lines showed higher productivity (20%), shorter internodes (11%) and a shorter distance between the first bunch and the ground (30%), relative to the control. Using dwarf lines to obtain mini-tomato hybrids was shown to be viable since the hybrids demonstrated better agronomic performance.